2014
DOI: 10.1016/j.ijcard.2014.04.270
|View full text |Cite
|
Sign up to set email alerts
|

International comparisons of the management of patients with non-ST segment elevation acute myocardial infarction in the United Kingdom, Sweden, and the United States: The MINAP/NICOR, SWEDEHEART/RIKS-HIA, and ACTION Registry-GWTG/NCDR registries

Abstract: ObjectivesTo compare management of patients with acute non-ST segment elevation myocardial infarction (NSTEMI) in three developed countries with national ongoing registries.BackgroundResults from clinical trials suggest significant variation in care across the world. However, international comparisons in “real world” registries are limited.MethodsWe compared the use of in-hospital procedures and discharge medications for patients admitted with NSTEMI from 2007 to 2010 using the unselective MINAP/NICOR [England… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 32 publications
1
51
0
1
Order By: Relevance
“…The emergence of primary PCI has dramatically improved outcomes for patients with STEMI in the last decade 11 12. The improvement in vessel patency and the higher rate of TIMI flow, and the reduction of fatal haemorrhagic stroke, are the key reasons for the success of primary PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of primary PCI has dramatically improved outcomes for patients with STEMI in the last decade 11 12. The improvement in vessel patency and the higher rate of TIMI flow, and the reduction of fatal haemorrhagic stroke, are the key reasons for the success of primary PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Although similar therapies were indicated for both ST-elevation MI (STEMI) and non-STEMI (NSTEMI), under-prescribing in prescribing for NSTEMI patients were shown in Europe and USA [37] highlighting the need to examine prescribing trends in other parts of the world. Previous studies have also demonstrated variations in CV prescribing especially in women, the elderly and ethnic minorities and across geographical regions [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The MINAP Academic Group's success is reflected in > 60 MINAP papers that have been published in the last 9 years, some of which have been presented in this report. Our group contributed significantly to this large research output and, significantly, established international collaborations with investigators across multiple centres in analysis of pre-hospital thrombolysis 503 and with the ACTION (USA) 57 and SWEDEHEART (Sweden) 55 investigators in ongoing comparative analyses. The outputs from these analyses have provided the first whole-country international comparisons of the management and outcomes of AMI, providing a new benchmark against which to assess service delivery in the UK.…”
Section: Clinical Disease Research Using Linked Bespoke Studies and Ementioning
confidence: 99%
“…Linkage to national EHRs will extend comparisons to include ambulatory care before and after admission for heart attack, non-fatal events and longer-term outcome Study 23: we identified that high numbers of patients hospitalised with STEMI who were eligible for nine evidence-based care components did not receive all components, and that these patients went on to experience higher rates of mortality 56 Outcomes research specifically designed to follow care into the primary care setting is warranted to quantify the full implication of CMOCs Study 24: we carried out analyses of data from national registries in the UK, Sweden and the USA. International comparisons identified significant differences in use of surgical interventions and use of some secondary prevention medications in the UK 57 Further studies are needed to better explain patterns of clinical practice within and outside the UK, such as rates of coronary angiography and PCI Study 25: in a study to determine the extent to which GPs offer recommended smoking cessation advice and pharmacological interventions to smokers after discharge from hospital with ACS, we found that fewer than one-quarter of smokers received smoking cessation interventions in the 3 months following discharge. Those who quit experienced fewer cardiac events than those who continued smoking 58 Future research, both in larger prospective epidemiological studies and in RCTs, of the promotion of general practice smoking cessation interventions, the association between interventions and cessation and the effects on long-term clinical outcomes is warranted…”
Section: Main Research Findings Research Recommendationsmentioning
confidence: 99%